Impact of Software Engineering Research on Modern Programming Languages. - Ryder, Barbara; Soffa, Mary Lou (Computer (00189162), 2008)
The article discusses a study which examined the impact of software engineering research on a select set of programming languages, such as Java, C++, Ada and Visual Basic. The researchers found that software engineering research has had an impact on the development of most of the features of programming languages. On the other hand, the researchers found little evidence that software engineering research influenced the development of concurrency as found in the programming languages they considered.